2020
DOI: 10.1111/gcbb.12773
|View full text |Cite
|
Sign up to set email alerts
|

Functional response of the soil microbial community to biochar applications

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 93 publications
0
33
0
Order By: Relevance
“…Different bacterial species show a different level of tolerance to salt even under the same phylum ( Yang et al, 2021 ). The response of the microbial community to biochar application is dependent on its type, duration, soil conditions, and properties, such as biochar pH and pyrolysis temperature ( Cho et al, 2016 ; Fan et al, 2020 ; Xu et al, 2021 ). Zhang et al (2021) has reported that increasing some phylum (Bacteroidetes, Gemmatimondetes, and Firmicutes) and bacterial communities showed tolerance and strongly structured with increasing salinity stress.…”
Section: Discussionmentioning
confidence: 99%
“…Different bacterial species show a different level of tolerance to salt even under the same phylum ( Yang et al, 2021 ). The response of the microbial community to biochar application is dependent on its type, duration, soil conditions, and properties, such as biochar pH and pyrolysis temperature ( Cho et al, 2016 ; Fan et al, 2020 ; Xu et al, 2021 ). Zhang et al (2021) has reported that increasing some phylum (Bacteroidetes, Gemmatimondetes, and Firmicutes) and bacterial communities showed tolerance and strongly structured with increasing salinity stress.…”
Section: Discussionmentioning
confidence: 99%
“…However, the magnitude and the consequence of biochar amendments is variable and depends not only on the physical and chemical properties of the biochar but also on the biological, physical, and chemical properties of the recipient soil (Liu et al 2016). A recent meta-analysis suggests that biochar additions generally increase the abundance of AM fungi and decrease the abundance of actinomycetes (Xu et al 2021). Previous studies with Formosa mine tailings support this suggestion, demonstrating that biochar-based amendments influence the microbial composition of the E. glaucus rhizosphere by increasing fungal biomass and decreasing actinomycete biomass (Trippe et al 2021).…”
Section: Biochar Amendments Influence Soil Microbial Communities and ...mentioning
confidence: 99%
“…On the other side, Steinbeiss et.al [97] investigated that yeast-derived and glucosederived biochar exposure to soil increased the respiration rate of soil microbes. Xu et.al [111] analyzed the reasons for the diversity of reactions of soil's heterotrophic respiration to biochar and found that biochar properties and amounts, climate conditions, exposure methods, and time make a difference. In another detailed study, the regulation of microbe community structure by biochar was analyzed.…”
Section: Artificial Carbon Materials Advance the Microbialmentioning
confidence: 99%